Observation of electric potential in organic thin-film transistor by bias-applied hard X-ray photoemission spectroscopy. (23rd February 2016) - Watanabe, Takeshi; Tada, Keisuke; Yasuno, Satoshi; Oji, Hiroshi; Yoshimoto, Noriyuki; Hirosawa, Ichiro
Abstract: The effect of gate voltage on electric potential in a pentacene (PEN) layer was studied by hard X-ray photoelectron spectroscopy under a bias voltage. It was observed that applying a negative gate voltage substantially increases the width of a C 1s peak. This suggested that injected and accumulated carriers in an organic thin film transistor channel modified the potential depth profile in PEN. It was also observed that the C 1s kinetic energy tends to increase monotonically with threshold voltage.